Use of carbon dioxide (CO2) laser radiation in exposure of implants (stage II): A metallography evaluation in dogs - Guimaraes, MVM; Niccoli, W.; Bottino, M. A.; Schwab, C. (Laser Inst Amer, 2002)
In this study we analyzed possible damages that vaporization from laser radiation could cause to implant material. Fifteen standard titanium implants, measuring 3.75 mm in diameter by 7 mm in length, were placed into the upper and lower jaws of three dogs according to Branemark's system. After osseointegration, all implants were exposed. In group I (control) conventional exposure with a punch was used; in group II, a CO2 laser with 2 W (power density: 256 W/cm(2); fluency: 0.077 J/cm(2), and a pulse mode of 0.30 ms) was used, and in group III 4 W (power density: 512 W/cm(2), fluency: 0.154 J/cm(2), and a pulse mode of 0.30 ms) was used. After vaporization, the cover screws were removed and sent for metallographic examination. The results showed that cover screws irradiated with 2 and 4 W power caused no superficial or microstructural alteration. The results also showed that the prescribed power densities, fluencies, and the use of the pulse mode were suitable for exposing implants without damage to tissue or implant material. (C) 2002 Laser Institute of America.
Keywords: osseointegrated implants; carbon dioxide laser; stage II exposed implants